Menelusuri Kampung Ondel-Ondel: Studi Mengenai Sistem Jaringan dan Sistem Kerja Ondel-Ondel Kramat Pulo - Akhirun, Layosibana; Septiady, Yophie (CV. Social Politic Genius (SIGn), 2022)
This study aims to provide an overview of the Kramat Pulo community’s network and the working system on performances of ondel-ondel. This study uses a qualitative approach. The data were collected using in-depth interviews, observation, and documentation. The data that has been obtained is then analyzed using qualitative inductive analysis. The results show that the ondel-ondel network system of the Kramat Pulo community consists of several divisions of roles: owners, managers, studio members, entrepreneurs, field coordinators, buskers, and the Government of the Special Capital Region of Jakarta. The network system then establishes and supports the ondel-ondel working system: ondel-ondel performances and ondel-ondel busking. Ondel-ondel performances are generally only practised once or twice weekly. In contrast, ondel-ondel busking activities are practiced daily by Kramat Pulo teenagers. On the other hand, the relationship between the studio owner and entrepreneur and Kramat Pulo teenagers who want to parade ondel-ondel for busking on the streets can be done in two ways: rental or profit-sharing. This relationship is based on a belief system maintained by the Kramat Pulo community. Therefore, it is recommended that the Government of the Special Capital Region of Jakarta make unique spots for Ondel-ondel performances. In addition, coordination is needed between the field coordinator and the Government of the Special Capital Region of Jakarta to arrange ondel-ondel busking activities routes to create order without losing cultural nuances. In this case, Betawi indigenous people carry out their traditions by parading ondel-ondel to surround the village.